Up-regulation of DNMT3b contributes to HOTAIRM1 silencing via DNA hypermethylation in cells transformed by long-term exposure to hydroquinone and workers exposed to benzene. (1st April 2020) - Zhang, Haiqiao; Yuan, Qian; Pan, Zhijie; Ling, Xiaoxuan; Tan, Qiang; Wu, Minhua; Zheng, Dongyan; Xie, Peien; Xie, Daxiao; Liu, Linhua
Highlights: HOTAIRM1 first increased and then decreased with the time of HQ treatment on TK6 cells or workers exposed to benzene. DNA hypermethylation induced by DNMT3b involves in the silence of HOTAIRM1 expression in HQ-MT cells. HOTAIRM1 expressionwas restored by reducing methylation levels of its promoter in HQ-MT cells treated with 5-AzaC or TSA. Knockout of DNMT3b increased expression of HOTAIRM1 and HOTAIRM1 promoter hypomethylation in HQ-MT cells. Abstract: Benzene exposure is a risk factor of acute myeloid leukemia (AML), during such carcinogenesis long non-coding RNAs (lncRNAs) are important epigenetic regulators. HOTAIRM1 (HOXA transcript antisense RNA, myeloid-specific 1) plays an indispensable role in the development of AML. Hydroquinone (HQ) is one major metabolite of benzene and its ideal replacement in toxicology research. But the influence of benzene or HQ on HOTAIRM1 expression in AML associated pathway is still unclear. In the TK6 cells with short-term exposure to HQ (HQ-ST cells) or long term HQ exposure induced malignant transformed TK6 cells (HQ-MT cells), the relationship between DNMT3b and HOTAIRM1 was explored. Comparing to counterparts, HOTAIRM1 expression was increased firstly and then decreased in HQ-ST cells, and definitely decreased in HQ-MT cells; while the expression change tendency of DNMT3b was in contrast to that of HOTAIRM1. Moreover, the average HOTAIRM1 expression of 17 paired workers being exposed to benzene within 1.5 years was increased, but that of the remaining 92 paired workers with longer exposure time was decreased. Furthermore, in 5-AzaC (DNA methyltransferase inhibitor) or TSA (histone deacetylation inhibitor) treated HQ-MT cells, the expression of HOTAIRM1 was restored by reduced DNA promoter methylation levels. HQ-MT cells with DNMT3b knockout by CRISPR/Cas9 displayed the promoter hypomethylation and the increase of HOTAIRM1, also confirmed in benzene exposure workers. These suggest that long term exposure to HQ or benzene might induce the increase of DNMT3b expression and the promoter hypermethylation to silence the expression of HOTAIRM1, a possible tumor-suppressor in the AML associated carcinogenesis pathway.